2013
DOI: 10.1126/science.1242902
|View full text |Cite
|
Sign up to set email alerts
|

Low Upper Limit to Methane Abundance on Mars

Abstract: International audienceBy analogy with Earth, methane in the Martian atmosphere is a potential signature of ongoing or past biological activity. During the past decade, Earth-based telescopic observations reported "plumes" of methane of tens of parts per billion by volume (ppbv), and those from Mars orbit showed localized patches, prompting speculation of sources from subsurface bacteria or nonbiological sources. From in situ measurements made with the Tunable Laser Spectrometer (TLS) on Curiosity using a disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…This supplementary material repeats some of that published earlier (33) that is here updated and extended to include discussion of the enrichment experiments, spectral difference plots, correlation results of the TLS methane measurements with a variety of observed quantities like relative humidity, water abundance, ground and surface air temperatures, etc., and finally to present arguments for ruling out terrestrial contamination.…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…This supplementary material repeats some of that published earlier (33) that is here updated and extended to include discussion of the enrichment experiments, spectral difference plots, correlation results of the TLS methane measurements with a variety of observed quantities like relative humidity, water abundance, ground and surface air temperatures, etc., and finally to present arguments for ruling out terrestrial contamination.…”
Section: Methodsmentioning
confidence: 74%
“…Using the current data, the published value of 0.18 ± 0.67 ppbv and the upper limit of 1.3 ppbv in Webster et al (33) should be revised to 0.88 ± 0.81 ppbv and 2.2 ppbv, respectively. Although the revised mean for this 6-sol group is 0.88 ppbv, at 95% confidence level the upper limit is 0.88 +1.645*SEM = 2.2 ppbv, because in this case a one-sided Student distribution needs to be considered for upper limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially the data measured in (Mumma et al 2009) indicate that the lifetime should be much shorter (Holmes et al 2015), perhaps as short as 200 days. The recent observations by the Mars Science Laboratory (MSL) at Gale Crater indicate a background level of 0.2-0.8 ppb (parts per billion), showing a seasonal pattern, and localized pulses of CH 4 reaching 10 ppb (Webster et al 2013(Webster et al , 2015. These observations suggest that at least two different kinds of emission processes produce the background and the pulses of methane, either through geology or (bio)geochemistry related processes, or combined.…”
Section: Organicsmentioning
confidence: 95%
“…Following initial null results (Webster et al, 2013) that limited methane values below 1 ppbv, SAM-TLS found evidence for large spikes of methane up to ~7 ppbv which persisted over relatively short timescales of tens of sols and a background concentration of methane of < 0.7 ppbv (Webster et al, 2015). This value was more than 3 times lower than predicted by the UV-CH 4 model and is less than can be explained by the discrepancy between pre-flight modelling of UV flux (Moores et al, 2007) and the observed UV flux (Smith et al, 2016).…”
Section: Martian Methane In the Light Of Remsmentioning
confidence: 99%